Dibalik Keputusan MK: Pengabdian kepada Masyarakat oleh Mahasiswa di Mahkamah Konstitusi - Agustinus Rustanta; Gabriella Chiquita; Jessika Aprilia; Zaneta Noel (Jurnal Pengabdian Pada Masyarakat, 2020)
BEHIND THE CONSTITUTIONAL COURT DECISION: COMMUNITY SERVICE BY STUDENTS AT THE CONSTITUTIONAL COURT. One of the social services done by students of Tarakanita Higher School has just finished. It was at the Constitutional Court, Jakarta. It is also the rarest event since it does not even happen in five years. It gave students of secretarial training opportunity to take part in this honorable event where they are given chance to perform their capability in trancribing every conversation took place during the sessions of presidential election despute 2019. There are 32 students joining in this special event. They are grouped into two shifts i.e. morning and evening shift. Each student is responsible to transcribe the conversation happened in all sessions. Several days before the sessions, they were briefed and trained to work in accordance with the standard of work of Constitutional Court. The conclusion is that students are able to join in any social services and their involvement is highly appreciated.